Development of plant‐based diets and the evaluation of dietary attractants for juvenile Florida pompano, Trachinotus carolinus L. (13th February 2017) - Rhodes, M.A.; Zhou, Y.; Salze, G.P.; Hanson, T.R.; Davis, D.A.
Abstract: Sustainable and profitable commercial aquaculture production of marine fish species is dependent on the development of sustainable protein sources as substitutes for expensive animal meals such as fishmeal (FM). Previous Florida pompano Trachinotus carolinus studies have indicated that poultry by‐product meal (PBM) and meat and bone meal can be used to produce a FM‐free diet if suitable levels of nutrients (such as taurine) are included in the diets. In this study, we attempted to develop an all‐plant protein diet by removing the animal proteins in practical diets for pompano by substituting back select ingredients. A series of eight FM‐free diets were formulated, four systematically replaced soybean meal (SBM) with soy protein concentrate (SPC) and four replaced PBM with SPC. Based on the results, there is no clear disadvantage to the use of SPC as a replacement for SBM. However, the complete removal of PBM resulted in reduced performance. Two additional growth trials were conducted to supplement additional amino acids including glycine, valine and histidine, a proprietary chemical attractant mix, fish protein concentrate and squid hydrolysate to improve the growth of pompano when fed all‐plant protein diets. The only improvement in performance occurred with the squid hydrolysate. These results demonstrate that using soybean meal, soy protein concentrate and corn gluten meal as the primary protein sources, a plant‐based feed formulation can be developed, but the removal of all animal proteins is not yet feasible.